Spatial S-R compatibility effects in an intentional imitation task. - Heyes, C; Ray, E (2004)
The active intermodal mapping hypothesis suggests that intentional imitation is mediated by a highly efficient, special-purpose mechanism of actor-centered movement encoding. In the present study, using methods from stimulus-response (S-R) compatibility research, we found no evidence to support this hypothesis. In two experiments, the performance of adult participants instructed to imitate actor-centered spatial properties of head, arm, and leg movements was affected by task-irrelevant, egocentric spatial cues. In Experiment 1, participants imitated using the same side of their bodies as did the model, and performance was less accurate when egocentric stimulus location was response incompatible than when it was response compatible. This effect was reversed in Experiment 2 when participants imitated using the opposite side of their bodies. These findings, in line with general process theories of imitation, imply that intentional imitation is mediated by the same processes that mediate responding to inanimate stimuli on the basis of arbitrary S-R mappings.